Breast pathology - Sanders, Melinda E.; Simpson, Jean F. (Consultant pathology series, 2014)
"Based on actual cases drawn from the extensive breast pathology consultation practice at Vanderbilt University Medical Center, Breast Pathology covers the full classification of breast tumors and focuses on especially challenging differential diagnoses or unusual and problematic morphologic presentations. Using a pattern-based approach, each case is presented as a difficult diagnostic choice with two or even three possible diagnoses for the pathologist. For each case there is a description illustrating an expert's diagnosis and analysis, along with commentary providing additional context on the evaluation of such specimens. The book places special emphasis on avoiding diagnostic pitfalls. Each case discussion is supported with several high quality color photomicrographs that facilitate an extensive visual history and learning experience. Brief references to the literature are also included"--Publisher's description